From thermoelectric bulk to nanomaterials: Current progress for Bi2Te3 and CoSb3. Issue 3 (26th October 2015) - Peranio, N.; Eibl, O.; Bäßler, S.; Nielsch, K.; Klobes, B.; Hermann, R. P.; Daniel, M.; Albrecht, M.; Görlitz, H.; Pacheco, V.; Bedoya‐Martínez, N.; Hashibon, A.; et al.
Abstract : Bi2 Te3 and CoSb3 based nanomaterials were synthesized and their thermoelectric, structural, and vibrational properties analyzed to assess and reduce ZT ‐limiting mechanisms. The same preparation and/or characterization methods were applied in the different materials systems. Single‐crystalline, ternary p‐type Bi15 Sb29 Te56, and n‐type Bi38 Te55 Se7 nanowires with power factors comparable to nanostructured bulk materials were prepared by potential‐pulsed electrochemical deposition in a nanostructured Al2 O3 matrix. p‐type Sb2 Te3, n‐type Bi2 Te3, and n‐type CoSb3 thin films were grown at room temperature using molecular beam epitaxy and were subsequently annealed at elevated temperatures. This yielded polycrystalline, single phase thin films with optimized charge carrier densities. In CoSb3 thin films the speed of sound could be reduced by filling the cage structure with Yb and alloying with Fe yielded p‐type material. Bi2 (Te0.91 Se0.09 )3 /SiC and (Bi0.26 Sb0.74 )2 Te3 /SiC nanocomposites with low thermal conductivities and ZT values larger than 1 were prepared by spark plasma sintering. Nanostructure, texture, chemical composition, as well as electronic and phononic excitations were investigated by X‐ray diffraction, nuclear resonance scattering, inelastic neutron scattering, Mössbauer spectroscopy, and transmission electron microscopy. For Bi2 Te3 materials, ab‐initio calculations together with equilibrium and non‐equilibrium molecular dynamics simulations for point defects yielded their formation energies and their effect on lattice thermal conductivity, respectively. Current advances in thermoelectric Bi2 Te3 and CoSb3 based nanomaterials are summarized. Advanced synthesis and characterization methods and theoretical modeling were combined to assess and reduce ZT ‐limiting mechanisms in these materials. Abstract : Current advances in thermoelectric Bi2 Te3 and CoSb3 based nanomaterials are summarized. Advanced synthesis and characterization methods and theoretical modeling were combined to assess and reduce ZT‐limiting mechanisms in these materials.